Burnout Among Generation Z in Creative Agencies: The Role of Work-Life Balance and Workload through Job Stress - Adilah Rahmah; Ilzar Daud; Pramana Saputra; Rizky Fauzan; Syahbandi Syahbandi (Economics and Digital Business Review, 2026)
The fast-paced work environment and project-related pressures in the creative agency sector may increase the risk of burnout among Generation Z employees. This study aimed to examine the effects of work-life balance (WLB) and workload on burnout, with work stress as a mediating variable. A quantitative approach was employed using a survey of 200 Generation Z employees working in creative agencies in Indonesia, selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicated that WLB had a negative and significant effect on work stress (β = -0.575; p < 0.001), whereas workload had a positive and significant effect on work stress (β = 0.502; p < 0.001). Workload and work stress also had positive and significant effects on burnout (β = 0.312; p < 0.01; β = 0.489; p < 0.001), while WLB did not have a significant direct effect on burnout (β = -0.124; p > 0.137). In addition, work stress mediated the relationships between WLB, workload, and burnout. These findings suggest that burnout among Generation Z employees in creative agencies is primarily shaped by work stress arising from excessive job demands, highlighting the importance of managing workload and promoting work-life balance to reduce burnout risk.